If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 + 8x = 2x + -1 Reorder the terms: 3 + x + 8x = 2x + -1 Combine like terms: x + 8x = 9x 3 + 9x = 2x + -1 Reorder the terms: 3 + 9x = -1 + 2x Solving 3 + 9x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 9x + -2x = -1 + 2x + -2x Combine like terms: 9x + -2x = 7x 3 + 7x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 7x = -1 + 0 3 + 7x = -1 Add '-3' to each side of the equation. 3 + -3 + 7x = -1 + -3 Combine like terms: 3 + -3 = 0 0 + 7x = -1 + -3 7x = -1 + -3 Combine like terms: -1 + -3 = -4 7x = -4 Divide each side by '7'. x = -0.5714285714 Simplifying x = -0.5714285714
| 5y+3(y-6)=3(y+2)-2 | | 3x+7=8x-13 | | (1/6)(8x-7)=(x+7/12) | | 2a-5b=38 | | -1(x-12)+2(x+3)=6(x+3) | | 6[9-(-3x-3)]=54x+108 | | P=c+3b+4aforc | | 7(4x-5)-3=28x-38 | | 8z-19=-15+7z | | 9x+8-7(x+1)=6x+4 | | -1(x-12)+2(x+3)=x+3 | | 4x=34+3x-5+7x | | 9x+1=9(x+9) | | 4x+9-67(x+1)=6x+7 | | x^3+3x^2-81x-85=0 | | -(7y+5)-(-6y-8)=0 | | (4/10x)-2x+(8/5)=(4/5) | | x/2-4=x/5-1 | | 87*28/29*4/9 | | 9x+21+x=5+x+5 | | 12+5n=62 | | -3(6x-5)+3=18x+18 | | 5y+8=48 | | 8x+3=8(x+7) | | 11/7=X/6 | | (2-3x)*(2-3x)=8 | | 0.14(y-3)+0.06y=0.10y-0.5 | | 9x+13=5x+89 | | x+18+21x=3x+9 | | x+28+21x=3x+9 | | 16(18m-4)=24m+8 | | 216-3x=42x+16 |